Comparing the durability of the long-lasting insecticidal nets DawaPlus® 2.0 and DuraNet© in northwest Democratic Republic of Congo - Paul Mansiangi; Solange Umesumbu; Irène Etewa; Jacques Zandibeni; Nissi Bafwa; Sean Blaufuss; Bolanle Olapeju; Ferdinand Ntoya; Aboubacar Sadou; Seth Irish; Eric Mukomena; Lydie Kalindula; et al. (Malaria Journal, 2020)
Abstract Background Anecdotal reports from DRC suggest that long-lasting insecticidal nets (LLIN) distributed through mass campaigns in DRC may not last the expected average three years. To provide the National Malaria Control Programme with evidence on physical and insecticidal durability of nets distributed during the 2016 mass campaign, two brands of LLIN, DawaPlus® 2.0 and DuraNet©, were monitored in neighbouring and similar health zones in Sud Ubangi and Mongala Provinces. Methods This was a prospective cohort study of representative samples of households from two health zones recruited at baseline, 2 months after the mass campaign. All campaign nets in these households were labelled, and followed up over a period of 31 months. Primary outcome was the “proportion of nets surviving in serviceable condition” based on attrition and integrity measures and the median survival in years. The outcome for insecticidal durability was determined by bio-assay from subsamples of campaign nets. Results A total of 754 campaign nets (109% of target) from 240 households were included in the study. Definite outcomes could be determined for 67% of the cohort nets in Sud Ubangi and 74% in Mongala. After 31 months all-cause attrition was 57% in Sud Ubangi and 76% in Mongala (p = 0.005) and attrition due to wear and tear was 26% in Sud Ubangi and 48% in Mongala (p = 0.0009). Survival in serviceable condition at the last survey was 37% in Sud Ubangi and 17% in Mongala (p = 0.003). Estimated median survival was 1.6 years for the DawaPlus® 2.0 in Mongala (95% CI 1.3–1.9) and 2.2 years for the DuraNet in Sud Ubangi (95% CI 2.0–2.4). Multivariable Cox proportionate hazard models suggest that the difference between sites was mainly attributable to the LLIN brand. Insecticidal effectiveness was optimal for DuraNet©, but significantly dropped after 24 months for DawaPlus® 2.0. Conclusions In the environment of northwest DRC the polyethylene LLIN DuraNet© performed significantly better than the polyester LLIN DawaPlus® 2.0, but both were ...